Microbial Concrete, a Wonder Metabolic Product That Remediates the Defects in Building Structures - Reddy, M.; Achal, V.; Mukherjee, Abhijit (Springer, 2012)
Microbes play key geoactive roles in the biosphere, particularly in the areas of element biotransformations, biogeochemical cycling and mineral transformations and formations. Recently, the ability of bacteria to produce minerals such as carbonates has been studied in detail with various uses in civil engineering. Natural processes, such as weathering, faults, land subsidence, earthquakes, andhuman activities create fractures and fi ssures in concrete structures, which can reduce the service life of the structures. ‘Microbial Concrete’ a novel metabolic byproduct of microbially induced calcite precipitation by way of urease (urea hydrolyzing enzyme) presents a promising novel biotechnology for the enhancement of durability of building materials and structures. The ubiquity and importance ofmicrobes in inducing calcite precipitation make “microbial concrete” a most important metabolic product of biomineralization that can remediate and restore such structures. Urease producing bacteria when added to cement, helps in the improvement of compressive strength, reduction of permeability and reduced corrosion rate of reinforced structure. The promising results using this metabolic product encouraged different research groups world wide and in-depth studies of these different approaches have been discussed in this chapter. The methodologies to such approach have also been discussed. The present chapter suggests a potential use of the microbially induced calcite precipitation process with environmental signifi cance as a safe consolidation tool in remediation of defects in building structures and towards enhancement in its service life.